Erratum to: Measurement of the W boson polarisation in t t ¯ events from pp collisions at √ s = 8 TeV in the lepton + jets channel with ATLAS (The European Physical Journal C, (2017), 77, 4, (264), 10.1140/epjc/s10052-017-4819-4) - Onofre, A. (2019)
A bug in the code used to calculate the total correlation coefficients between the W boson helicity fractions obtained using the leptonic analyser in semileptonic tt¯ events in the region with ≥2 b-tags was found. It led to quoting incorrect correlation coefficients in the original paper. The correct correlation coefficients are ρF0,FL=−0.82 , ρF0,FR=−0.97 and ρFL,FR=+0.65. This change does not have any impact on the measured helicity fractions, but it changes the obtained limits on the anomalous couplings.